APPLICATION PRACTICE OF THE ORDER OF THE RUSSIAN MINISTRY OF HEALTH IN THE ORDER OF THE ORGANIZATION OF SANATORIUM TREATMENT (on the example of sanatorium for children) - Shipova, V.M.; Berseneva, E.A.; Gadzhieva, S.M. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Medit͡s︡ina, 2017)
The analysis of recommendations of the Russian Ministry of Health about regular provid-ing the sanatorium organizations is provided to publications, reducing standard number of average and associate health workers is shown.